1998
DOI: 10.1016/s0194-5998(98)70377-8
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Clinical Evaluation in Pediatric Obstructive Sleep Apnea

Abstract: Eighty-two children underwent polysomnography (PSG) for symptoms suggestive of obstructive sleep apnea (OSA). Symptoms reported included snoring, witnessed apneic episodes, daytime somnolence, mouth breathing, and enuresis. Tonsillar size, nasal airway patency, and percentile weight were recorded. OSA was diagnosed on PSG when obstructive events were noted and apnea + hypopnea index was five or more per hour. The overall predictive accuracy of clinical suspicion of OSA was 25 (30%) of 82. Predictive accuracies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
0
12

Year Published

1999
1999
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(97 citation statements)
references
References 17 publications
4
81
0
12
Order By: Relevance
“…Most otolaryngologists make decisions or recommendations based on medical history that is suggestive of SDB, as well as on physical examination demonstrating adenoid and/or tonsillar hypertrophy [2,[8][9][10]. However, predictive accuracy of clinically suspected OSAS may be as low as 30% when PSG testing was performed as well [13,19]. Unlike polysomnography that measures derangements in physiologic parameters during sleep in obstructive children, the SS, like other health-related clinical surveys, focuses on the physical problems and functional limitations consequent on upper airway obstruction as reported by caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…Most otolaryngologists make decisions or recommendations based on medical history that is suggestive of SDB, as well as on physical examination demonstrating adenoid and/or tonsillar hypertrophy [2,[8][9][10]. However, predictive accuracy of clinically suspected OSAS may be as low as 30% when PSG testing was performed as well [13,19]. Unlike polysomnography that measures derangements in physiologic parameters during sleep in obstructive children, the SS, like other health-related clinical surveys, focuses on the physical problems and functional limitations consequent on upper airway obstruction as reported by caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…34 Numerous studies investigating the validity of using history and physical examination alone to establish an OSA diagnosis have found that they are poor predictors of OSA. [35][36][37][38][39][40][41][42] Additional studies have evaluated the usefulness of questionnaires to identify OSA. One such questionnaire is the OSA-18, which is a disease-specific quality-of-life questionnaire commonly used by pediatric otolaryngologists.…”
Section: Discussionmentioning
confidence: 99%
“…A prevalence rate of 8-47% of NE was reported by some studies [66][67][68][69][70] in comparison to a prevalence rate of 2-15% in children without upper airway obstruction [71][72][73][74]. A high resolution rate of childhood nocturnal enuresis has been associated with tonsillectomy and/or adenotonsillectomy [64,66,[75][76][77][78][79][80][81][82][83].…”
Section: Ne and Upper Airway Obstruction Are They Related?mentioning
confidence: 99%